The Relationship between Dietary Compliance, Physical Activity, and Nutritional Status with the Incidence of Type 2 Diabetes Mellitus in Adults in the Barong Tongkok Health Center Work Area - Jessica Hanason, Arielle; K, Iriyani; Larene Safika, Erri (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Diabetes Mellitus is a metabolic syndrome disease that causes high mortality rates both nationally and internationally. The prevalence of diabetes mellitus in adults aged 15 years and over in West Kutai Regency in 2018 showed a figure of 1.86% for diabetes mellitus sufferers. Objective : This study aims to determine the relationship between dietary compliance, physical activity, and nutritional status with the incidence of type 2 diabetes mellitus in adults in the Barong Tongkok Health Center work area. Research Methods/ Implementation Methods : The type of research used is cross-sectional with a total of 77 respondents. Data collection using a questionnaire. Data were analyzed using the Fisher Exact test. Results : The results showed that there was a significant relationship between dietary compliance (p <0.001), physical activity (p <0.045), and nutritional status (p <0.001) with the incidence of type 2 diabetes mellitus in adults in the Barong Tongkok Health Center work area with a p-value <0.005. Conclusion/Lesson Learned : This study concludes a relationship between dietary compliance, physical activity, and nutritional status with the incidence of type 2 diabetes mellitus in adults. It is recommended that there is a need for dietary regulation, regular exercise, weight monitoring, and blood sugar monitoring to live a healthy life.